How Can China’s Indium Resources Have a Sustainable Future? Research Based on the Industry Chain Perspective - Jing Lin (MDPI AG, 2021)
Global competition and storage for indium resources are increasing. This paper uses substance flow analysis to quantify the flow of indium in China from 2000 to 2019 and discusses the problems facing China’s indium industry chain. Over the past 20 years, China has mined more than 21,000 tons of indium from the lithosphere, and the accumulated indium content in imported ore is about 3600 tons. In the upper reaches of the industrial chain, the loss of indium exceeded 19,000 tons; in the middle reaches, due to technical barriers, China exported a large amount of indium at low prices and imported a large amount of ITO targets at high prices. The amount of indium in the imported targets exceeded 2100 tons; in the downstream, approximately 60% of the final products were exported abroad. China’s cumulative output of recycled indium was about 630 tons, primary indium output was 5912 tons, and the cumulative inventory of indium reached 3200 tons. Therefore, increasing the recovery rate in the primary production stage, overcoming the technical barriers in the middle of the industry chain, and establishing an efficient recovery system are necessary measures to promote the sustainable development of indium resources and its industry chain.